Spectroscopic Confirmation of a Massive Protocluster with Two Substructures at z ≃ 3.1 - Michael J. Nicandro Rosenthal; Amy J. Barger; Lennox L. Cowie; Logan H. Jones; Stephen J. McKay; Anthony J. Taylor (The Astrophysical Journal)
We present the results of a Keck and Northern Extended Millimeter Array spectroscopic survey of 507 galaxies, where we confirm the presence of two massive overdensities at z = 3.090−3.110 and z = 3.133−3.155 in the neighborhood of the GOODS-N, each with over a dozen spectroscopically confirmed members. We find that both of these have galaxy overdensities of near-infrared-detected galaxies of δ _gal,obs = 6−9 within corrected volumes of (6−7) × 10 ^3 cMpc ^3 . We estimate the properties of the z = 0 descendants of these overdensities using a spherical collapse model and find that both should virialize by z ≃ 0.5−0.8, with total masses of M _tot ≃ (6−7) × 10 ^14 M _⊙ . The same spherical collapse calculations, as well as a clustering-of-clusters statistical analysis, suggest a >80% likelihood that the two overdensities will collapse into a single cluster with M _tot = (1.0−1.5) × 10 ^15 M _⊙ by z ~ 0.1−0.4. The z = 3.14 substructure contains a core of four bright dusty star-forming galaxies with ΣSFR = 2700 ± 700 M _⊙ yr ^−1 in a volume of only 280 cMpc ^3 .